Sistem Kendali Kecepatan Kendaraan Berdasarkan Kondisi Cuaca Pada Daerah Karawang Dengan Menggunakan Metode Fuzzy Logic - Putra, Habib Alhamdi; Nurpulaela, Lela (Peneliti.net, 2023)
Motor vehicles operating on highways can encounter varying weather conditions such as rain, fog, or other adverse weather conditions. Poor weather conditions can significantly affect safety and travel efficiency. Therefore, in this research, we propose a vehicle speed control system that can adjust the speed based on the prevailing weather conditions in the Karawang region. The method employed in this study is Fuzzy Logic. Fuzzy Logic is a control method that allows us to describe the uncertainty and ambiguity associated with complex problems like weather conditions. By utilizing Fuzzy Logic, we can mathematically represent linguistic variables such as